Evidence for changing intimate partner violence safety planning needs as a result of COVID-19: results from phase I of a rapid intervention. (May 2021) - Metheny, N.; Perri, M.; Velonis, A.; Kamalanathan, J.; Hassan, M.; Buhariwala, P.; Du Mont, J.; Mason, R.; O'Campo, P.
Abstract: Objectives: The aim of the study was to examine the need for modified safety planning strategies in response to COVID-19–related increases in intimate partner violence (IPV) as the initial phase of adapting an IPV safety planning intervention in Toronto, Ontario. Methods: A rapid, systematic review was conducted to elucidate existing safety planning strategies used during public health emergencies. These were supplemented with strategies from an expert panel. A survey of IPV survivors and service providers gauged the helpfulness of each strategy during COVID-19. Results: Together, the systematic review and expert panel yielded 26 conceptually distinct strategies, which were evaluated by 111 IPV survivors and providers. Of these, 19 (69%) were 'highly recommended', 3 (12%) were 'somewhat recommended' and 6 (23%) were not recommended for use during the COVID-19 pandemic because they might make the violence worse. Conclusions: Safety planning needs have changed owing to the effect of COVID-19 on IPV incidence, service provision and risk factors, as well as policies restricting freedom of movement. These results will be used to modify an existing IPV safety planning mobile application for use during COVID-19 and future public health emergencies.